What Type Relationship Do We Have with Our Brands? Is The Name of This Relationship Brand Romance? - Hatice Aydın; Cemal Zehir (International Review of Management and Marketing, 2017)
Consumers' loyalty to a brand depends on their establishing an emotional relationship with it. This relationship may be called as brand romance. Many factors influence the emergence of brand romance (ROM), including brand novelty (BN), brand satisfaction (BS), and subjective brand knowledge (SBK). The present study evaluates brand romance dimensions such as pleasure, arousal and dominance in terms of these antecedents and outcomes as attitudinal and behavioral brand loyalty. The study was carried out with 295 consumers in Istanbul/Turkey via face-to-face questionnaires. In this study, BS, SBK, and BN have a positive influence on arousal and pleasure dimensions of brand romance whereas the effect of SBK is not statistically significant on dominance dimension of brand romance. Also arousal and dominance dimensions of brand romance are positively effective on behavioral and attitudinal loyalty whereas pleasure dimension is not statistically significant on behavioral loyalty. Keywords: Brand Romance, Subjective Brand Knowledge, Brand Novelty, Brand Satisfaction, Brand Loyalty